Effect of composite biodegradable biomaterials on wound healing in diabetes - Ren, Sihang; Guo, Shuaichen; Yang, Liqun; Wang, Chenchao (Frontiers in Bioengineering and Biotechnology, 2022)
The repair of diabetic wounds has always been a job that doctors couldn't tackle quickly in plastic surgery. To solve this problem, it has become an important direction to use biocompatible biodegradable biomaterials as scaffolds loaded with a variety of active substances or cells, to construct a wound repair system integrating materials, cells, and growth factors. In the research of wound healing, a variety of studies have pointed to the application of composite biodegradable biomaterials in drug release, tumor-targeted therapy, and gene therapy. In terms of wound healing, composite biodegradable biomaterials show strong biocompatibility and the ability to promote wound healing. This review describes the multifaceted integration of biomaterials with drugs, stem cells, and active agents. In wounds, stem cells and their secreted exosomes regulate immune responses and inflammation. They promote angiogenesis, accelerate skin cell proliferation and re-epithelialization, and regulate collagen remodeling that inhibits scar hyperplasia. In the process of continuous combination with new materials, a series of materials that can be well matched with active ingredients such as cells or drugs are derived for precise delivery and controlled release of drugs.